Perancangan Fasilitas Duduk Moveable untuk Lansia - Mia Arianti Nuriman; Grace Mulyono; Poppy Firtatwentyna Nilasari (Intra, 2018)
In performing both indoor and outdoor activities, elderly will experience distress due to the decreased physical condition. Therefore, they will need extra time and energy and tends to get tired and feel sore when doing various activities (such as sitting, walking, or standing for too long). The problems found were analyzed along with the theories that have been obtained, to create a product in order to help elderly to perform various activities. This product can help and make elderly feel more comfortable in doing their activities.Design method used is the design thinking process from Interaction Design Foundation which consists of 3 stages: Inspiration (Understand, Observe), Ideation (Ideate, Prototype, Test), and Implementation (Story-telling, Business model).From the problems existed, the products were designed and produced in the form of a movable seating facility for elderly that is easy to move around and suitable for both outdoor and indoor. The design of this product is different with the other products because it is equipped with additional facilities such as storage / bag, walking stick that can be used as the grip of walker as well, and a sella stick or 4 leg stick. Moreover, this chair can also be folded and stored in a narrow place. This seating facility has an ergonomic aspect that has been adjusted to the ergonomics of elderly to make sure that they would feel comfortable.